(untitled) (Journal of the College of Basic Education, 2022)
The study aimed at identifying the level and effectiveness of the performance and scientific enlightenment of the players of the League for handball, effectively forecasting performance in terms of the enlightenment scientific and Sports of the players of the League for handball, researchers struck a descriptive approach in a relational database relations, a sample of the players of the participating clubs league for handball stadium (2015-2016), the (176), the player of selected intentional neglect by (100%) of the community of origin, were divided into three samples, researchers resorted to the design of a form of performance assessment and test the enlightenment of the Scientific according to a series of steps and the determinants of the methodology of acceptance, after the application of the Scandisk Instrument Cluster in this study, researchers concluded that the Scandisk Instrument cluster (calendar form effective performance, and testing of enlightenment scientific) valid for measuring the players of the Premier League For handball, and the players of the League for handball have enlighten scientific clear, and linked to the scientific enlightenment for handball performance effectively positive relationship and contribute to the improvement of the players of the League for handball, can predict the effectiveness of the performance of the players of the handball through scientific game